X-ray photoelectron spectroscopy of reduced graphene oxide prepared by a novel green method. (September 2015) - Rella, Simona; Giuri, Antonella; Corcione, Carola Esposito; Acocella, Maria Rosaria; Colella, Silvia; Guerra, Gaetano; Listorti, Andrea; Rizzo, Aurora; Malitesta, Cosimino
Abstract: This work is focused on the surface characterization of reduced graphene oxide (rGO) obtained through reduction of graphite oxide. The reduction was performed using a green method (based on UV irradiation under N2 ) with low environmental impact, free of additional functionalization reagents, simple and low-cost. X-ray photoelectron spectroscopy (XPS) was applied for chemical characterization of surface C species showing a significant reduction of oxygen-containing functional groups from the surface of rGO. Highlights: Surface characterization of graphene obtained through reduction of graphite oxide. Reduction by a green method. Chemical characterization by X-ray photoelectron spectroscopy.